Radiotherapy for Head and Neck Cancer in Lombardy: A Survey by the Lombardy Group of the Italian Association for Radiation Oncology. Issue 5 (September 2015) - Merlotti, Anna; Di Muzio, Nadia; Antognoni, Paolo; Filippone, Francesco; Bianchi, Ernestina; Castiglioni, Simona; Bruschieri, Lorenza; Lvaldi, Giovanni; De Cicco, Luigi; Marzoli, Luca; Orecchia, Roberto
Aims: In 2013, a survey was conducted to analyze the available resources and their use in the radiation treatment of patients with malignancies of the head and neck region in Lombardy, on behalf of the Lombardy group of the Italian Association of Radiation Oncology. Methods: A questionnaire was sent to 26 of 34 radiotherapy centers active in the region. Two centers were excluded because they did not treat head and neck cancers (Besta Neurological Institute and Cyberknife center), 4 had started their activity in 2013 or late 2012, and 2 satellite centers had their results included in the main center's response. Items investigated included number of patients with head and neck cancer treated in 2012, general technical issues, and integration with surgery and chemotherapy. Results: Twenty-four questionnaires were returned (92% response rate). There was a good consistency on the use of radiotherapy in different settings, whereas integration with chemotherapy showed more heterogeneous data. Treatment techniques were 3D conformal radiotherapy or intensity-modulated radiotherapy with image-guided radiotherapy in most cases and a low rate of treatment-related death was observed. Conclusions: This survey provides important data on the use of radiotherapy resources for patients with head and neck cancer in Lombardy. The data offer the opportunity to further investigate issues that could better standardize head and neck cancer treatment and allocate resources across the region.